Price discovery and the accuracy of consolidated data feeds in the U.S. equity markets - Brian F. Tivnan; David Slater; James R. Thompson; Tobin A. Bergen-Hill; Carl D. Burke; Shaun M. Brady; Matthew T. K. Koehler; Matthew T. McMahon; Brendan F. Tivnan; Jason G. Veneman (Journal of Risk and Financial Management, 2018)
Both the scientific community and the popular press have paid much attention to the speed of the Securities Information Processor-the data feed consolidating all trades and quotes across the US stock market. Rather than the speed of the Securities Information Processor (SIP), we focus here on its accuracy. Relying on Trade and Quote data, we provide various measures of SIP latency relative to high-speed data feeds between exchanges, known as direct feeds. We use first differences to highlight not only the divergence between the direct feeds and the SIP, but also the fundamental inaccuracy of the SIP. We find that as many as 60% or more of trades are reported out of sequence for stocks with high trade volume, therefore skewing simple measures, such as returns. While not yet definitive, this analysis supports our preliminary conclusion that the underlying infrastructure of the SIP is currently unable to keep pace with the trading activity in today's stock market.
Keywords: 330; market microstructure; price discovery; latency